The equivalence of income and consumtpion taxes: are money illusion, loss aversion and salience the spoilsports - Tesing, Tobias (2022)
Classic economic theory suggests the equivalence of sales and income taxation. However, Blumk in, Ruffle, and Ganun (2012) find in a real-effort experiment that subjects reduce their la-bor supply more in response to an income tax than to an equivalent sales tax. Using an adjusted experiment design, this paper aims to (i) replicate this result, (ii) test whether money illusion and/or loss aversion are the underlying behavioral biases, and (iii) examine the impact of the non-salience of sales taxes on labor supply. My difference-in-difference estimates do not con-firm the results in Blumk in, Ruffle, and Ganun (2012). Moreover, money illusion, loss aversion and the non-salience of sales taxes do not appear to influence labor-leisure decisions. I arguethat my adjusted experimental design may represent a more realistic approach and that the effect observed in Blumk in, Ruffle, and Ganun (2012) may be too small to have real-world implications.